Poly-flex-antennas: Application of polymer substrates in flexible antennas - Praveen Kumar Sharma; Jae-Young Chung (eXPRESS Polymer Letters)
The proliferation of flexible electronics has entirely transformed the field of antenna design and paved the door for cutting-edge uses in communication, sensing, and other areas. The present research lends a succinct overview of the intriguing advancements in flexible antenna technology, with specific emphasis on the implementation of polymer substrates. As we refer to poly-flex antennas in this article, they stand for the incorporation of polymer substrates in antenna design. Polymer substrates are the optimum candidate for flexible antenna applications as they have specific advantages, including being lightweight, conformable, and inexpensive. The main features of poly-flex antennas, such as their design concepts, fabrication processes, and performance characteristics, are being explored in this proposed article. We delve into the wide variety of polymer substrates that are appropriate for antennas, taking into account their dielectric characteristics, flexibility, and environmental resistance. Their dielectric characterization, bending effects, challenges, and future prospects of this burgeoning field are also addressed. We conclude by emphasizing the immense potential of poly-flex-antennas to shape the future of wireless communication and sensing systems, and how the adoption of polymer substrates is driving innovation in antenna engineering.